Моделювання системи контролю технологічного процесу виготовлення господарського мила - Григоренко, Ігор Володимирович; Андрєєв, Денис Артемович; Кондрашов, В. С. (Черкаський державний технологічний університет, 2023)
The result of the computer simulation of the control system of the technological process of the production of laundry soap using the Lab VIEW software package is presented for conducting research related to the determination of optimal metrological operating modes of the system that affect the quality of finished products.
Keywords: інформаційно-вимірювальні системи; мило; температура; контроль; управління; household soap; measurement; temperature; sensor; error